Factors of exposure, experience in the traffic and previous involvements in traffic accidents among college students of health courses, Ponta Grossa, PR, Brazil - Labiak, Valéria Beatris; Leite, Maysa de Lima; Virgens Filho, Jorim Sousa das; Stocco, Caroliny (Saúde e Sociedade, 2008)
The most frequent type of victims in traffic accidents is youngsters, mainly of the masculine sex. This high incidence has been attributed to age-related behaviors that could make youngsters transgress traffic laws and, consequently, provoke accidents. Thus, the present study aimed to describe the socioeconomic and demographic profile, besides characterizing the exposure and antecedents in traffic accidents, of college students of Health courses of the State University of Ponta Grossa - PR, in 2005. A questionnaire, answered by the students anonymously, was used, whose sample included 624 academics. The studied variables were: demographic and socioeconomic characteristics, exposure factors and experience in the traffic, use of the seat belt and antecedents in traffic accidents. The students' profile was characterized as follows: the majority is of the female sex (66.67%), with ages ranging between 18 and 23 years, living with the family and with income equal to or below 10 minimum wages. In relation to the age they learned how to drive, the largest frequency in the masculine sex was between 15 and 17 years and in the feminine sex, 18 years or above. A significant number of subjects, from both sexes, reported having learned to drive when they were less than 14 years of age. The association between the use of the belt and the place occupied in the car (driver, passenger of the front seat and passenger of the back seat), according to the sex, revealed that the use of the device does not depend on the sex. The association between involvement in traffic accidents and sex indicated a predisposition in the masculine sex.